Bimbingan dan Konseling Karir Di PAUD - oki Lukmanul Hakim (Program Studi Pendidikan Islam Anak Usia Dini, 2023)
This research was conducted as an effort to find out the implementation of guidance and counseling, especially in the field of early childhood career guidance and counseling in PAUD. This is based on the importance of implementing career guidance and counseling in early childhood education units, which are intended to direct children so they can achieve their career awareness. The subjects involved in this study were teachers and students of PAUD Al Ihya Tasikmalaya City. The things studied in this study are the implementation of career guidance at PAUD Al Ihya Tasikmalaya City. The focus of the study is described in a number of questions as follows: 1) how is the guidance and counseling process particularly related to careers for early childhood at PAUD Al Ihya Tasikmalaya City?, 2) in the implementation of career counseling guidance for early childhood at PAUD Al Ihya Tasikmalaya City, using what media?; in this study using a qualitative approach in research activities. Data and information collection techniques are carried out through observation, interviews and documentation. Based on the results of qualitative data analysis, it shows that the implementation of career guidance at PAUD Al Ihya Tasikmalaya City can be said to have been carried out, but it needs development so that it can measure the ability of knowledge about careers, in the use of media, the media used is appropriate and according to standards, so the aim is to grow Career awareness in early childhood runs optimally.